QUALITY STUDY OF HUMAN DEVELOPMENT AND POVERTY IN MADURA ISLAND - Dwi Susilowati; Sri Joko; Risky Angga Pramuja (Jurnal Ekonomi Pembangunan, 2019)
This study aims to find out the most dominant factors and determine the districts in Madura that require special attention from the observed model so that it can provide benefits for policymakers, and the research method used is panel data with the OLS square approach. The results of panel data regression with the fix effect model show the results that the variables that have a positive and significant influence are the GRDP at a 5% confidence level in the GRDP variable with a positive direction while the open unemployment variable has a significant negative effect having a 6% confidence level with a negative direction. Variable consumption expenditure does not have a significant effect but has a positive direction. Intercept values differ in each district which shows the uniqueness of the model of the fixed effect. The highest intercept values were Pamekasan Sampang, Bangkalan and Sumenep. From the results of the HDI classification, the Sampang has a low classification of the district vocationally on Madura Island. The results of the classification of expenditure of basic and lowest consumption of staples in 2012 and 2018 were Pamekasan and Sumenep. The results of the classification of the highest open unemployment rates were in Bangkalan in 2012 and 2018. The lowest GRDP classification was in Pamekasan districts in 2012 and 2017.